The cartesian equation of the line through the points (1,2,3) which is parallel to the vector 4 ̂i + 2 ̂j + 6 ̂k is given by- |
(x-1)/4 = (y+2)/2 = (z-3)/6 (x+1)/4 = (y-2)/2 = (z-3)/6 (x-1)/4 = (y-2)/2 = (z+3)/6 (x-1)/4 = (y-2)/2 = (z-3)/6 |
(x-1)/4 = (y-2)/2 = (z-3)/6 |
We have vector a = ̂i + 2 ̂j + 3 ̂k and vector b = 4 ̂i + 2 ̂j + 6 ̂k Therefore vector equation of the line is given by- vector r = a+λb ⇒ r = ( ̂i + 2 ̂j + 3 ̂k)+λ (4 ̂i + 2 ̂j + 6 ̂k) ⇒ r = (1+ 4λ) ̂i + (2+2λ) ̂j + (3+ 6λ) ̂k ⇒ x ̂i + y ̂j +z ̂k = (1+ 4λ) ̂i + (2+2λ) ̂j + (3+ 6λ) ̂k Eliminating λ, we get (x-1)/4 = (y-2)/2 = (z-3)/6
|